Peaceful coexistence between Muslims and Christians in Baitul Maqdis between 1897-1994: Manifestations, effects and challenges / Ibrahim Saqer Ismail Alzaeem - Ibrahim Saqer , Ismail Alzaeem (2016)
Muslim-Christian coexistence in the city of Bait Al-Maqdis is a sophisticated phenomenon that is worth a careful study in order to extract the benefits of this experience which can be realized by revealing the reasons and impacts on the city of Bait Al-Maqdis and its people, to be a role model across nations, cultures and religions. This study, then, analyses the harmonic coexistence, its features, effectiveness and challenges, between Muslims and Christians in the City of Bait Al-Maqdis between (1897-1994) aiming to investigate the extent of the importance of the City of Bait Al-Maqdis to both Muslims and Christians. Moreover, it seeks to identify the Muslim and Christian presence in the City of Bait Al-Maqdis. It also identifies the social and political characters of the coexistence between Muslims and Christians. It studies the roles of Muslims and Christians in confronting the Zionist plan. The study examines the effect of challenges and future of Muslim-Christian coexistence in the City of Bait Al-Maqdis on the resistance to Israeli occupation. Therefore, historical and descriptive methods as well as interviews were applied for the research methodology. The findings reveals that Muslims and Christians of the City of Bait Al-Maqdis have succeeded in promoting the values of understanding and national partnership, and in establishing the basics of resisting the Zionist ambitions through adopting the Arab rights and mutual resistance at all levels to defend the Islamic and Christian holy places despite the political changes that took place in the city during the British mandate and the Israeli occupation in 1967 that led to difficulties at all aspects of life.